The Development of Basic Wudhu Mobile Application for Johor Islamic School in Year 3 Pupils - Mohd Afandi, Nur Iman; Kamsan, Siti Zulalina; Ishak, Muhammad Isham Fareez; Kassim@Kasim, Noordiana (Multidisciplinary Applied Research and Innovation, 2022)
This paper will discuss the Islamic application that we built for students in Year 3 in Sek Agama Johor about Wudhu which is under the subject Ibadat. This research paper discusses on the subject of E-learning as a computer-based teaching tool, as it is currently increasingly often being utilized in all educational levels, especially during times when face to face interaction is not permissable. Teaching and learning in an e-learning environment differs from traditional classrooms learning environment and might bring new problems to teachers and students especially for those who are left behind in areas of technology. The purpose of this paper is to describe how our application works and highlight the e-learning concept through our application. The method that has been used for this apps development is the System Development Life Circle (SDLC) and the effectiveness result of our project can be seen through the questionnaires that we did on teachers and parents.